Influence of Paylater and Flashsale on Impulse Buying Behavior among Adult Women in Semarang City - Irin Mirrah Luthfia (Admisi dan Bisnis, 2023)
The development of digital technology has introduced Paylater as a payment system that allows purchases to be made in period of payment. Flash sale is a marketing strategy where products or services are offered at a highly discounted price for a limited time. Paylater services and discount offers in Flashsale sales can encourage consumer behavior by providing flexible payment options and getting low prices. This research uses Multiple Linear Regression method by distributing questionnaires to a sample of 30 adult women aged 19-44 years in Semarang City. The results of this study indicate that Paylater and Flashsale, individually, have a positive and significant influence of 52.5% and 43% respectively on Impulse Buying behavior. Additionally, they have a simultaneous influence of 26.3% on Impulse Buying behavior. This means that payment through Paylater and flash sale moments trigger consumers to engage in Impulse Buying.